Developments in Multi-Agent Fair Allocation - Aziz, Haris (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
Fairness is becoming an increasingly important concern when designing markets, allocation procedures, and computer systems. I survey some recent developments in the field of multi-agent fair allocation.